1997
DOI: 10.1021/es960903l
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of Volatile Organic Compounds in Pressed Humic Acid Disks

Abstract: The slow sorption and desorption of volatile organic compounds (VOCs) in soils are assumed to be partly controlled by intraparticle diffusion and diffusion in soil organic matter (SOM) and influence soil remediation. In this study, humic acid, a component of SOM, is used to simulate SOM as a partition medium for VOCs. The sorption kinetics of VOCs in dry, pressed humic acid disks was investigated by tracking the weight change of the sorbent with a microbalance. A diffusion model successfully describes the kine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
53
4

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(74 citation statements)
references
References 25 publications
(32 reference statements)
17
53
4
Order By: Relevance
“…3 and 4). Similar studies by Chang et al [17] on the rate of sorption-desorption of VOCs by HS, revealed that the sorption of toluene onto HA, an integral member of a soil HS, is found to be reversible and diffusion controlled. Shih and Wu [39] reported that partitioning is believed to be the major mechanism of the sorption of toluene in HS.…”
Section: Hasupporting
confidence: 68%
See 1 more Smart Citation
“…3 and 4). Similar studies by Chang et al [17] on the rate of sorption-desorption of VOCs by HS, revealed that the sorption of toluene onto HA, an integral member of a soil HS, is found to be reversible and diffusion controlled. Shih and Wu [39] reported that partitioning is believed to be the major mechanism of the sorption of toluene in HS.…”
Section: Hasupporting
confidence: 68%
“…Chang et al [17] investigated the sorption kinetics of toluene, n-hexane, and acetone using dry, pressed HA disks and they reported that the sorption of volatile organic compounds (VOCs) by HA is a physical process and that the slow process of sorption in natural soils is not entirely a consequence of diffusion. In this study we investigated the sorption of toluene by HAs extracted from Chengching Lake sediment and Meifong Mountain soil.…”
Section: Introductionmentioning
confidence: 99%
“…The gravimetric method with a microbalance has been used to trace the time courses of sorption of VOCs on soil organic matter [13][14][15] and on oven-dried clay [16,17], all under dry conditions. However, the major constraint associated with gravimetric methods for the investigation of sorption dynamics is the inability to observe the behavior at the molecular level or under a wet condition.…”
Section: Introductionmentioning
confidence: 99%
“…Volatile organic compounds (VOCs) are slowly sorbed into soil particles, and some of them could be retained in soil constituents over a long period of time [1][2][3]. This phenomenon has been attributed to the slow diffusion through soil micropore structures [5][6][7], through matrixes formed by condensed organic matter [8,9], and through the soil organic matter (SOM) [10][11][12]. This heterogeneity affects the prediction of the activity and fate of a pollutant.…”
Section: Introductionmentioning
confidence: 99%
“…The sorption of toluene in humic acid and humin extracted from Yangmingshan (Taiwan) soil has been found to be reversible and diffusion controlled [12,19]. Humic acid and kaolinite were selected as the two model soil components to represent SOM and soil inorganic matter (SIM).…”
Section: Introductionmentioning
confidence: 99%